ION VATAMANU: ORIGINALITATE DE GÂNDIRE ŞI DE TEHNICI LIRICE CULTIVATE - Grosu, Lidia (CEP USM, 2008)
Though he has not been alive for a long time, we cannot talk of Ion Vatamanu in the past. He is rushing into a flight, full of restlessness, being determined to put his interior experiences into words. The harmonious combination of the letters with the real sciences emphasizes the severe analytical spirit, which denotes the permanent tendency to reflect the reality through poetical fresh and deep vision, based on the pragmatic intellect of a well-informed research person. The poet Ion Vatamanu was and will remain one of the patriot poets, a person with verticality of reformations, he will remain the person of innovation and aspiration to the progress both scientifically and culturally, although in his evolution he was suppressed by the totalitarian censorship, as a result of which he had to suffer a lot.